Social media analysis in the context of social responsibility approach of football fan groups - Şirin, Tayfun; Eryilmaz, Fahri; Eratli Şirin, Yeliz; Aydin, Özge; Metin, Mehmet (Frontiers in Psychology, 2025)
As one of sectors that address social problems, sports can pioneer very useful social responsibility efforts with its wide area of influence. Participation in social responsibility projects, especially through popularity of football, reaches much wider audience. It is seen that unofficial fan groups, which are already part of society, can direct very different sports stakeholders with their leadership positions that will affect large masses. Although it is important for this leadership to be done with active participation, it is also fact that it can be much more effective with creative and innovative projects. By examining initiatives in which in general football fans are involved within framework of social responsibility as stakeholders of football, it can be understood which problems in social area are more important from perspective of football fans. Thus, in future, much higher level of benefit can be provided for social problems by using such resources much more effectively and efficiently. In this context, this study was conducted with aim of examining social responsibility-focused Instagram posts of fan groups of three most important sports clubs operating in sports in Turkey in context of participation, leadership, innovation and creativity. In line with purpose of the study, Instagram pages, which run by fan groups, examined belong to Beşiktaş club’s Çarşı and UNIBJK fan groups, Fenerbahçe club’s Genç Fenerbahçeliler and UNIGFB fan groups, and Galatasaray club’s ultrAslan and UAUNI fan groups. 150 Instagram posts from each fan group, dating back to April 12, 2021, and total of 900 posts, were examined through content analysis. In content analysis, social responsibility-focused posts were coded and evaluated. In general, it was observed that the posts were made on axis of Agenda-Setting Approach. It is seen that social responsibility is increasingly becoming strategic necessity among sports stakeholders and is also used as means of strengthening legitimacy. In addition to leadership provided in terms of participation, it has been determined that there are areas that need to be improved in terms of creativity and innovation.